Transformasi Ekonomi di Jazirah Arab: dari Era Pra-Islam Hingga Masa Nabi Muhammad - T, Tasriani; Ritonga, Miftahul Janna; Aini, Fauqah Nuri; Hidayat, Mhd. Nanang (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article discusses the socio-cultural and economic transformation of Arab society from the era of Jahiliyyah to Islamic civilization under the leadership of Prophet Muhammad (peace be upon him). Before Islam, Arab society lived in a state of social disorder, characterized by a strong tribal structure, injustice, and idol worship practices. The arrival of Prophet Muhammad (peace be upon him) brought fundamental changes through the teachings of monotheism, equality, and social justice. The migration to Medina marked the beginning of a more structured Islamic society, with the Charter of Medina serving as the first constitution that regulated inter-tribal relations and ensured harmony among different religious communities. This study employs the library research method. The findings reveal that Islamic teachings successfully transformed the social order of Arab society into one that is more just, harmonious, and civilized, significantly contributing to the development of world civilization.